2022
DOI: 10.1111/tbed.14642
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the hurdles that remain for control of African swine fever in smallholder farming settings

Abstract: To honour the 100 years anniversary of the first publication about African swine fever (ASF) a webinar with a particular focus on disease control in the smallholder sector was organized. This article is based on the webinar, summarizing the early history of ASF research, reflecting on the current global disease situation and bringing forward some suggestions that could contribute towards achieving control of ASF.The first description of ASF by R. Eustace Montgomery in 1921 laid the foundations for what we know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Smallholder farmers in developing countries such as Timor-Leste with chronic poverty and lack of veterinary services, often experience high pig mortalities from diseases, particularly during major outbreaks ( 11 , 22 24 ). Low investment in pig farming leads to low biosecurity, which in turn leads to higher disease risk ( 9 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smallholder farmers in developing countries such as Timor-Leste with chronic poverty and lack of veterinary services, often experience high pig mortalities from diseases, particularly during major outbreaks ( 11 , 22 24 ). Low investment in pig farming leads to low biosecurity, which in turn leads to higher disease risk ( 9 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Barnes et al ( 9 ) reported similar benefits from engaging farmers and technicians in feeding trials and biosecurity practices in Timor-Leste. Chenais et al ( 22 ) and Aliro et al ( 26 ) recommended greater support for community education and participatory methods that take into account local social and cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of a need to prioritise vaccine development for ASF, millions of poor households, especially in sub-Saharan Africa but also in the Asia-Pacific region and the Caribbean, keep pigs as a coping mechanism [ 58 , 134 , 136 , 185 , 186 , 187 , 188 , 189 ] or because of their cultural importance [ 190 ]. The utility of a vaccine in these settings is questionable, especially in the lower income countries where help from government is of necessity limited by lack of resources.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognised that biosecurity measures need to be developed in partnership with the pig owners and other stakeholders in the value chain to ensure that they are financially feasible, culturally acceptable, and, thus, implemented [ 23 , 27 , 30 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. The arrival of ASF in Eastern Europe, the Asia-Pacific region and, most recently, the Caribbean, has provided a new impetus for research that focuses on the specific circumstances and possibilities for pig keeping and disease management in the smallholder sector.…”
Section: Introductionmentioning
confidence: 99%
“…This is understandable and important, considering the impact that ASF has on commercial pig production and international trade. It is nevertheless believed that the benefits of those advancements will vary in the smallholder sector, depending on limitations such as genotype variation versus homologous vaccine protection, thermostability, costs, and practical applications [ 21 , 53 , 58 ]. There is also a growing body of literature on antiviral substances that are active, at least in vitro, against ASFV, but this does not appear to offer short-term solutions for management of ASF in the resource-limited smallholder sector.…”
Section: Introductionmentioning
confidence: 99%